2015
DOI: 10.1089/end.2014.0317
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Best Method to Evaluate Urine pH? A Trial of Three Urinary pH Measurement Methods in a Stone Clinic

Abstract: The hand-held pH device gave urinary pH readings that most closely and consistently matched those of the reference bench-top laboratory machine. This method of pH measurement should be considered in stone clinics in patients with pH-dependent stone risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
2
8
1
1
Order By: Relevance
“…1 , 2 , 3 , 4 ). However, the precision of our averaged pH dipstick reading is essentially the same as that found by Ilyas et al [ 10 ] when they compared 200 individual dipstick pH readings to laboratory pH meter. This indicates that we likely have reached the limits of precision achievable by dipstick pH monitoring, but dipsticks are not sufficiently precise to guide clinical management.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…1 , 2 , 3 , 4 ). However, the precision of our averaged pH dipstick reading is essentially the same as that found by Ilyas et al [ 10 ] when they compared 200 individual dipstick pH readings to laboratory pH meter. This indicates that we likely have reached the limits of precision achievable by dipstick pH monitoring, but dipsticks are not sufficiently precise to guide clinical management.…”
Section: Discussionsupporting
confidence: 79%
“…Kwong et al [ 4 ] tested 390 urine samples with both urinary dipstick and electrochemical pH meter and concluded that dipsticks had an unacceptable frequency of clinically relevant error. Similarly, Ilyas et al [ 10 ] compared a clinic-based portable pH meter, urinary dipsticks, and litmus paper to laboratory-based pH meter and found that dipsticks lacked the precision needed to base a clinical decision. However, to our knowledge, our study is the first to look beyond single dipstick pH readings in an attempt to account for diurnal variation in urinary pH.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some dipsticks in our study were of unacceptable repeatability for pH. Some previous literature reports have also demonstrated unacceptable precision and accuracy of the dipsticks comparing them with gold standard, pH – meter ( 26 ). It has also been reported that dipsticks vary in accuracy due to proportions and combinations of the reagents (like methyl red and bromthymol blue) in pH fields provided by different manufacturers ( 27 ).…”
Section: Discussioncontrasting
confidence: 53%
“…20) In the studies comparing accuracy and reproducibility between benchtop pH meter and portable pH meters, portable pH meters had nearly perfect agreement with the benchtop pH meter. 20,21) In the current study, the salivary pH measurements using pH paper showed adequate agreement with those using pH meter. However, pH paper exhibited lower pH values compared to those by pH meter (paired t-test, p<0.001; Table 3).…”
Section: Discussionsupporting
confidence: 64%